2022
DOI: 10.12669/pjms.39.1.5679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paroxetine hydrochloride combined with idebenone on inflammatory factors and antioxidant molecules in treatment of depression after ischemic stroke

Abstract: Objectives: To evaluate the effects of paroxetine hydrochloride combined with idebenone on inflammatory factors and antioxidant molecules in the treatment of depression after ischemic stroke. Methods: Randomized controlled trial was adopted on 80 patients with depression after ischemic stroke were randomly divided into two groups, with 40 patients in each group at Xingtai Sanli Health Quannan Clinic from March 17, 2019 to December 20, 2021. Both groups were given basic treatment. On this basis, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have shown that the antidepressant effects of all the above-mentioned drugs are almost equivalent and the safety is very high, but paroxetine has a quick effect and is more selective to 5-HT and it can bind to G proteincoupled receptor kinase 2. The inhibitory effect occurs more directly and the myocardial contractility of heart after myocardial infarction is also improved [6] . Therefore, paroxetine has more research value.…”
mentioning
confidence: 99%
“…Studies have shown that the antidepressant effects of all the above-mentioned drugs are almost equivalent and the safety is very high, but paroxetine has a quick effect and is more selective to 5-HT and it can bind to G proteincoupled receptor kinase 2. The inhibitory effect occurs more directly and the myocardial contractility of heart after myocardial infarction is also improved [6] . Therefore, paroxetine has more research value.…”
mentioning
confidence: 99%